The rise of energy accumulated in metal nanopowders; Technical Physics; Vol. 57, № 8 - Ilyin A. P. Aleksandr Petrovich (2012, 2012)
The influence of nanopowder irradiation by fast (4-MeV) electrons on the energy stored in nanopowders is studied. It is found that the irradiation of the nanopowders increases the amount of accumulated energy by 2.5 times as a maximum compared with the thermal effect of nonirradiated nanopowder oxidation.